Over The Top Services - A Review Paper (Trinity Journal of Management, IT & Media (TJMITM), 2022)
OTT (over-the-top video streaming) services have revolutionized the way which  consumers watch television. Understanding how video-on-demand (VoD)  technology progresses and what consequences might be projected from the  continued use of VoD is becoming more important for an information system’s  long-term viability. The study is primarily concerned with whether or not current  SVOD subscribers want to maintain using the service in the long run. Subscription  video on demand (SVOD) is an over-the-the-top (OTT) service where users  may access media content via a variety of innovative delivery methods made  possible by advances in information and communication technology (ICT). An  investigation into OTT services and video on demand (VoD), the OTT and VoD  market in India, and the impact of covid-19 on OTT platforms are discussed in  the study. User retention in Information Systems relies heavily on their ability to  stay engaged with a product or service over time. Service providers and content  creators alike are reaping the benefits of the growing popularity of over-the-top  (OTT) streaming services.
Keywords: ITC; OTT Platforms; Video on Demand; subscription-based video on demand; Subscription intentions; behavioral intentions